Unsettled peace? The territorial politics of roadbuilding in post-war Sri Lanka. (January 2020) - Ruwanpura, Kanchana N.; Chan, Loritta; Brown, Benjamin; Kajotha, V.
Abstract: This paper analyses the role of roadbuilding as a process of state territorialisation in post-war Sri Lanka. In the aftermath of a brutal civil war (1983–2009), and in lieu of a broader peace and reconciliation process between Sinhalese, Tamil and Muslim communities, road infrastructure has been promoted by the state as essential to the region's recovery and nation's sovereignty. Roads were to bring national unity and political integration. We interrogate such claims, drawing on fieldwork conducted in Jaffna and neighbouring areas to cast doubt on the prospects of new roads to ameliorate ethnic tensions. Rather, as militarised security discourses and policies continue to dominate the Sri Lankan public sphere, such schemes can be understood as part of broader Sinhala-Buddhist nationalist project to consolidate territorial control in restive parts of the country. Our research suggests that, rather than facilitating rehabilitation and recovery, road networks mirror pre-existing fault lines and entrench the privileged position of the military in Sri Lankan society. Such shifts do little to avail persistent minority sentiments of political marginalisation, aggravating social fractures and re-constituting the hegemony of Sinhala-Buddhist nationalism.